Introduction to educational research : a critical thinking approach - Suter, W. Newton , 1950- (SAGE, 2012)
"Introduction to educational research: a critical thinking approach 2e is an engaging and informative core text that enables students to think clearly and critically about the scientific process of research. In acheiving its goal to make research accessible to all educators and equip them with the skills to understand and evaluate published research, the text examines how educational research is conducted across the major traditions of quantitative, qualitative, mixed methods, and action research. The text is oriented toward consumers of educational research and uses a thinking-skills approach to its coverage of major ideas"